"Perfectly proper and conciliating": Jean-Pierre Boyer, freemasonry, and the revolutionary Atlantic in eastern Connecticut, 1800–1801. Issue 3 (3rd July 2019) - Hinks, Peter P.
ABSTRACT: Near the end of the Quasi-War in 1800, Jean-Pierre Boyer, future president of Haiti, was brought to New London, Connecticut with other partisans from the pro-French forces in St. Domingue. Boyer along with others were held in nearby Norwich until April 1801. A Freemason, Boyer was welcomed by Masons in Norwich while plundered by other Masons on the cruiser and in New London. In 1800, internal contention roiling Masonry in New London County readily overlapped with local political partisanry and religious controversy – all of which likewise engaged broader regional and national conflicts. The insertion of a black French partisan initiated into a foreign Masonic order enriched the presence of the Atlantic in all these contests. This essay explores how Boyer and Freemasonry helped to highlight the complex web of local, national, and Atlantic interpenetrating the political and social life of New London County.